Association between iron deficiency anemia and risk of venous thromboembolism: a multi-institutional retrospective study - Hung, Kuo-Chuan; Weng, Hsiu-Lan; Hsu, Chih-Wei; Lai, Yi-Chen; Chen, I-Wen (Frontiers in Nutrition, 2025)
BackgroundIron deficiency anemia (IDA) represents the most prevalent nutritional deficiency globally, affecting approximately one-third of the world’s population. Despite its widespread occurrence, the association between IDA and venous thromboembolism (VTE) remains inadequately characterized. This study aimed to comprehensively evaluate the relationship between IDA and VTE risk using real-world clinical data.MethodsWe conducted a multi-institutional retrospective cohort study utilizing the TriNetX platform to analyze electronic health records from 2010 to 2023. The study included 180,484 propensity-matched pairs, comparing patients with confirmed IDA to controls with dermatitis/eczema. Matching incorporated demographic, clinical, and laboratory variables to minimize confounding. The primary outcome was 1-year VTE risk, with secondary outcomes including all-cause mortality, intensive care unit (ICU) admission, upper extremity thrombosis, and thrombocytosis development. A mechanistic analysis excluded patients developing thrombocytosis to assess potential mediating pathways.ResultsPatients with IDA demonstrated a 75% increased risk of VTE within 1 year compared to controls (hazard ratio [HR]: 1.75, 95% confidence interval [CI]: 1.58–1.94, p < 0.001). The association varied by VTE subtype, with pulmonary embolism showing a more pronounced relationship (HR 2.05, 95% CI: 1.76–2.38, p < 0.001) than deep vein thrombosis (HR 1.54, 95% CI: 1.35–1.75, p < 0.001). Risk was highest during the initial 3 months post-diagnosis (HR 2.09, 95% CI: 1.67–2.62, p < 0.001). When patients developing thrombocytosis were excluded, VTE risk was substantially attenuated (HR 1.19, 95% CI: 1.05–1.33, p = 0.004), suggesting reactive thrombocytosis mediates a significant portion of the excess risk. The thrombotic risk extended beyond traditional VTE sites, with upper extremity thrombosis occurring 2.5-fold more frequently (HR 2.50, 95% CI: 1.77–3.53, p < 0.001). IDA was also associated with increased mortality (HR 2.12, 95% CI: 1.93–2.32, p < 0.001) and ICU admission (HR 1.67, 95% CI: 1.52–1.83, p < 0.001).ConclusionThis large-scale study establishes IDA as a significant modifiable risk factor for VTE, with peak risk occurring early after diagnosis. The findings support enhanced clinical vigilance and consideration of prophylactic strategies for IDA patients, particularly during initial months following diagnosis.